Structural Equation Modeling , Perceived Risk and Flow State: a study in e-commerce - Costa, Cristiane Salomé Ribeiro; Lucian, Rafael (Revista Gestão da Produção Operações e Sistemas, 2008)
Flow theory is being presented as a relevant construct for understanding consumer behavior in online environments. Perceived risk has been the subject of academic studies as an inhibitor of online purchases. Thus, the goal of this research is to investigate the relationship between the perception of risk and the flow state. The method adopted was descriptive through an online questionnaire with a sample of 196 respondents. Modeling of structural equation revealed that the ability of consumers using the Internet interferes in their perception of risk. It was also observed that there is no relationship between flow and risk perception. Keywords: Flow; Perceived risk; Structural equation modeling.